Microstructural Mechanical Analysis of Warm-Mixed Reclaimed Semiflexible Pavement Materials with Interfacial Weakening Effect - Hua Tan; Weian Xuan; Huang Wenke (Advances in Materials Science and Engineering)
Warm-mixed reclaimed asphalt pavement technology, as an environmental recycling method to reuse waste materials, has been widely investigated around the world. However, the skeleton of the reclaimed asphalt mixture is unstable due to the existence of the reclaimed materials. Semiflexible pavement has been successfully used in heavy traffic area due to its high rutting resistance. For combination with these two methods, a warm-mixed reclaimed semiflexible pavement material was proposed in this study. In order to investigate the interfacial weakening effect of the warm-mixed reclaimed semiflexible pavement material in a microstructural perspective, an image-based two-dimensional microstructural finite element model was presented. Results show that the maximum compressive stress of the new and RAP aggregates and cement mortar with interface is greater than that without interface and the compressive stress of the material increases when considering the interface. Besides, the maximum compressive strain of the material with interface is greater than that without interface and the strain values in the models with interface at all three positions are greater than those without interface.